Development and performance analysis of intelligent fault ride through control scheme in the dynamic behaviour of grid connected DFIG based wind systems. (November 2020) - Raghavendran, C.R.; Preetha Roselyn, J.; Devaraj, D.
Abstract: As the penetration of wind power increases, the fault ride through requirements imposed by grid code is important in grid connected wind systems. The wind systems should remain connected to the grid during grid faults satisfying the grid code which ensures grid stability during fault and post fault conditions. This paper proposes an intelligent fault ride through strategy for Doubly Fed Induction Generators (DFIG) based Wind Energy Conversion Systems (WECS) to achieve real and reactive power control during grid faults. The transient behaviour of the system is investigated under normal conditions and during grid faults. A fuzzy based wind speed estimation method in Maximum Power Point Tracking (MPPT) mode under normal conditions and coordinated Genetic Algorithm based Real-Reactive (GA-PQ) controller with DC chopper in Fault Ride Through (FRT) mode during grid faults is developed in this work. The proposed control scheme provides smooth operation of DFIG during grid faults by controlling the rotor and grid side converters, providing reactive power support to the grid and relieving stress on power converters thereby achieving system stability. The proposed strategy maintains the system parameters during the grid faults by suppressing the rotor and stator over current, dc link voltage overshoot, power oscillations and support the grid voltage under both balanced and unbalanced grid fault conditions with different voltage dips at PCC. Computer simulations in time-domain are performed by verifying the MPPT and FRT capability of the proposed strategy for 6.5MW grid connected DFIG based WECS in MATLAB/SIMULINK 2018b. The proposed coordinated intelligent PQ and DC chopper FRT strategy is compared against existing FRT schemes like crowbar, SDBR, DC Chopper, PQ controller and its hybrid combinations which yields satisfactory results. The proposed scheme is also validated in Opal-RT hardware for LLG fault at 75% dip in voltage. The simulation and real time results observed in the work station demonstrates the effectiveness of the proposed strategy in enhancing the FRT capability of the system.